Performance characteristics of multiparametric-MRI at a non-academic hospital using transperineal template mapping biopsy as a reference standard - Chau,EM; Arya,M; Petrides,N; Aldin,Z; Mckenzie,J; Emberton,M; Virdi,J; Ahmed,HU; Kasivisvanathan,V (International Journal of Surgery Open, 2018)
ObjectivesTo evaluate diagnostic accuracy of mpMRI in a non-academic hospital using transperineal template prostate mapping (TPM) biopsy as a reference standard. Secondary objectives included evaluating why mpMRI missed significant cancer.Materials and methods101 men received pre-biopsy mpMRI and TPM-biopsy over 16 months. Disease status was assigned at hemigland level. Primary histological definition of clinical significance was Gleason grade >/ = 4 + 3 or maximum cancer core length (MCCL) >/ = 6 mm. Positive mpMRI was defined as Prostate Imaging Reporting and Data System (PI-RADS) score >/ = 3.ResultsMedian age 69 (IQR 62–76). Median PSA 7 ng/ml (IQR 4.6–9.8). mpMRI had sensitivity 76.9%, specificity 60.7%, PPV 40.4% and NPV 88.3% at primary definitions. For detecting any Gleason >/ = 7 mpMRI had sensitivity 73.2%, specificity 60.3%, PPV 41.4% and NPV 85.4%. Mean MCCL was lower where significant cancer was missed compared to those correctly identified (5.8 mm versus 7.7 mm respectively, p = 0.035).ConclusionmpMRI performance characteristics were very encouraging when compared to contemporary clinical trials. In a non-academic hospital setting, negative mpMRI was just as good at ruling-out significant disease, though the ability of positive mpMRI to accurately detect significant disease was lower. An mpMRI-guided diagnostic pathway should be accompanied by appropriate mpMRI protocol optimisation, training, and quality control.